Pengaruh Model Teams Games Tournament (TGT) berbasis Permainan Bowling dan Kartu terhadap Hasil Belajar IPS - Nur Endah Litasari; Diyah Ayu Retnoningsih (STKIP AL HIKMAH SURABAYA, 2022)
Based on the results of the initial data analysis in the research, several problems were found, including a lack of student activity in asking questions, teachers needing tools in social studies lessons, a lack of variety in learning models, students tend to get bored because teachers only use the lecture method which in the end students' scores are still below the KKM score. This research aims to find the influence of the Teams Games Tournament (TGT) learning model based on Bowling and Card Games on the social studies learning outcomes of class V MI NU 01 Prupuk Selatan. This research is experimental. This type of research uses a quantitative approach with experimental methods and a quasi-experimental design using The Nonequivalent Pretest-Posttest Control Group. Data analysis techniques use validity, reliability, normality tests, homogeneity tests, and simple regression tests. The results of the research show that there is an influence of the Teams Games Tournament (TGT) learning model based on bowling and cards on the social studies learning outcomes of class V MI NU 01 Prupuk Selatan. The resulting influence is 54.20%.